2018
DOI: 10.1016/j.intfin.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Media censorship and stock price: Evidence from the foreign share discount in China

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 87 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, having less association with domestic business, foreign media outlets are relatively independent and objective and thereby play a more critical role in corporate governance (Dyck et al, 2008). Additionally, as pointed out by Ding et al (2018), the ratio of positive to negative news is substantially higher for Chinese media than for other regions' media due to the strict media censorship.…”
Section: Institutional Background and Hypothesis Developmentmentioning
confidence: 87%
See 1 more Smart Citation
“…Meanwhile, having less association with domestic business, foreign media outlets are relatively independent and objective and thereby play a more critical role in corporate governance (Dyck et al, 2008). Additionally, as pointed out by Ding et al (2018), the ratio of positive to negative news is substantially higher for Chinese media than for other regions' media due to the strict media censorship.…”
Section: Institutional Background and Hypothesis Developmentmentioning
confidence: 87%
“…Moreover, by showing that the intensity of investor reactions to news reports varies with media location, we propose a new explanation for why two share classes, listed in different markets but identical with respect to company fundamentals and shareholder rights, differ in capital costs and return rates. Aside from prior theories of market microstructure (Chan, Menkveld, & Yang, 2008), investment vehicle limitations (Sun & Tong, 2000), information exploitation (Li, Brockman, & Zurbruegg, 2015), analyst recommendations (Jia et al, 2017), and press censorship (Ding, Hou, Liu, & Zhang, 2018), the price difference may be attributed to investors' local media preference.…”
Section: Introductionmentioning
confidence: 99%
“…There were found significant relation, which shows that more freedom of the press and lower level of stock price synchronicity, enhancing information conditions of stock markets [26]. Another study in the field of stockiest prices suggested that free press enables free market disclosure with a more rapid market reaction [27]- [28], while media censorship affects foreign share discounts and international capital flows [29]. On the entity level, countries with freer media have more chances that corporate social responsibility activity enhances the value of local firms [30] as well as is considered a business environment and obstacles less significant [31].…”
Section: Review Of Literaturementioning
confidence: 91%